Organization of health care for military personnel with chronic viral hepatitis in Russian Armed Forces - K. V. Zhdanov; D. A. Gusev; K. V. Kozlov; M. S. Talantseva (Журнал инфектологии)
In article presents modern system of medical care to servicemen with chronic viral hepatitis. Also presented comparative analysis of the specialized care for these patients up to 2010 (prior to deployment in the clinic of infectious diseases of the Military Medical Academy center for the treatment of chronic viral hepatitis) and after. Shows that from 2007 to 2009. proportion of chronic viral hepatitis in the structure of all infectious diseases in the Armed Forces increased (in 2007 – 2.1%, in 2008 – 2.3%, in 2009 – 2.5%). Particularly significant increased incidence of contract servicemen. In 2007 – 5.2%, 2008 – 5.8% 2009 6 -%). Since 2010 there has been a strong tendency to reduce the incidence of chronic viral hepatitis in the structure of infectious diseases in general: 1.2% – in 2010, 0.8% – in 2011, and contract servicemen in particular: 4% – in 2010, 2.8% – in 2011, In addition, the article described in detail the steps and the amount of medical care for these patients.